Research on the Application of PBL Teaching Method in Physics Experiment Teaching (Global Journal of Human-Social Science, 2021)
Discuss the method and effect of problem-based teaching method (PBL) in the teaching of physics experiment in junior high school. Method: A total of 92 students in two junior high school classes were selected, and one of them was randomly set as the experimental group (46 students) and the other one was the control group (456 students). The experimental group added PBL teaching on the basis of traditional teaching methods. Methods, the control group was taught according to the traditional teaching method only, and finally the teaching effect of the two groups was compared. Results: The physics performance of the experimental group was significantly higher than that of the traditional teaching group (P
Keywords: physics teaching; experiment course; PBL teaching method